Workshop on Making Edpuzzle-Based Teaching Material Videos - Supianti, In In; Yaniawati, Poppy; Firmansyah, Eka; suminar, Chandra Siti; Pujiastuti, Sulastri (Journal of Community Research and Service, 2023)
There is a change in how teachers teach and students learn, which was initially done face-to-face at school, but now can be done online. The use of interactive learning media still needs to be improved due to the need for mastery of technology owned by teachers. Many teachers still need to understand practical learning applications for teachers and students. Students become less interested in participating in distance learning activities due to the limited use of various applications. So PKM activities were held as training workshops for making Edpuzzle-based teaching materials. The workshop was held for four days and involved 236 participants from various regions in Indonesia, such as Samarinda, Pekanbaru, and several areas in West Java. The activity method is divided into three steps: 1) preparation, 2) implementation, and 3) evaluation. Evaluation results based on questionnaire data show that 71% of teachers are assisted in monitoring student learning progress, and teachers can implement their work into learning.